Alterations in Circulating Immune Cells in Neovascular Age-Related Macular Degeneration - Lechner, Judith (Sci Rep, 2015)
Neovascular age-related macular degeneration (nAMD) is the leading cause of irreversible blindness in developed countries. Recent advances have highlighted the essential role of inflammation in the development of the disease. In addition to local retinal chronic inflammatory response, systemic immune alterations have also been observed in AMD patients. In this study we investigated the association between the frequency of circulating leukocyte populations and the prevalence as well as clinical presentations of nAMD. Leukocyte subsets of 103 nAMD patients (most of them were receiving anti-VEGF therapy prior to enrolment) and 26 controls were analysed by flow cytometry by relative cell size, granularity and surface markers. Circulating CD11b(+) cells and CD16(hi)HLA-DR(−) neutrophils were significantly increased (P = 0.015 and 0.009 respectively) in nAMD when compared to controls. The percentage of circulating CD4(+) T-cells was reduced in nAMD patients without subretinal fibrosis (P = 0.026) compared to patients with subretinal fibrosis. There was no correlation between the percentage of circulating leukocytes and the responsiveness to anti-VEGF therapy in nAMD patients. Our results suggest that higher levels of circulating CD11b(+) cells and neutrophils are associated with nAMD and that reduced levels of CD4(+) T-cells are associated with the absence of subretinal fibrosis in nAMD.